2019
DOI: 10.1002/pssa.201900818
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 2D Electron Gas Mobility in an AlN/GaN/AlN Double‐Heterojunction High‐Electron‐Mobility Transistor by Epilayer Stress Engineering

Abstract: Herein, 2D electron gas (2DEG) enhancement in an AlN/GaN/AlN double‐heterojunction high‐electron‐mobility transistor (DH‐HEMT) is achieved by epilayer stress engineering. The epistructures are grown on a SiC substrate using plasma‐assisted molecular beam epitaxy (PA‐MBE). The stress in the AlN buffer is systematically studied as a function of the III/V ratio. An optimized AlN buffer layer with the relaxation of 66% and a smooth surface morphology with a root mean square (RMS) roughness of 0.5 nm is grown using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…Hall-effect measurements in Van der Pauw configuration were performed on the as-grown heterostructure, demonstrating a room temperature 2DEG concentration of 3 • 10 13 cm −2 and electron mobility of 723 cm 2 /V•s, resulting in a sheet resistance of 293 Ω/sq. This measured mobility is close to the highest mobilities reported in the AlN/GaN/AlN structure of around 750 cm 2 /V•s [17]- [22]. To study the observed mobility limitations and the potential effect of the 2-dimensional hole gas (2DHG) that forms at the GaN channel/AlN buffer interface, the GaN channel for the heterostructure in this report was increased from 30 nm [18] in thickness to 200 nm.…”
Section: Epitaxial Growth and Device Fabricationsupporting
confidence: 68%
“…Hall-effect measurements in Van der Pauw configuration were performed on the as-grown heterostructure, demonstrating a room temperature 2DEG concentration of 3 • 10 13 cm −2 and electron mobility of 723 cm 2 /V•s, resulting in a sheet resistance of 293 Ω/sq. This measured mobility is close to the highest mobilities reported in the AlN/GaN/AlN structure of around 750 cm 2 /V•s [17]- [22]. To study the observed mobility limitations and the potential effect of the 2-dimensional hole gas (2DHG) that forms at the GaN channel/AlN buffer interface, the GaN channel for the heterostructure in this report was increased from 30 nm [18] in thickness to 200 nm.…”
Section: Epitaxial Growth and Device Fabricationsupporting
confidence: 68%
“…Figure 5c shows the temperature dependence of 2DEG mobilities. The mobilities for the thin‐barrier structure are 650 and 1100 cm 2 Vs −1 at 300 and 10 K. These values are comparable with mobilities reported previously [ 12–14,17,18 ] in these AlN/GaN/AlN heterostructures. In contrast, the 2DEG mobilities in the in situ‐passivated AlN/GaN/AlN heterostructure are 350 and 600 cm 2 Vs −1 at 300 and 10 K. It is 2 × lower than the thin barrier sample throughout the measured temperature range, albeit at a 1.5 × higher charge density.…”
Section: Resultssupporting
confidence: 89%
“…Simultaneously, a thinner GaN channel layer in the AlN/GaN/AlN structure has been found to result in a lower 2DEG room‐temperature mobility μ normaln . This experimental trend is supported independently both by data from controlled studies in our group and by literature reports [ 11–14,17 ] of AlN/GaN/AlN heterostructure growths. Interestingly, this trend is independent of the epitaxial growth method (e.g., metal organic chemical vapor deposition vs. MBE) and the starting substrates (Si, SiC, sapphire, bulk AlN).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…[13][14][15] AlN, as an ultrawide bandgap materials, is being investigated for use as a buffer in HEMT structures to address this problem. [16][17][18][19][20][21] This large band offset with the GaN channel layer offers not only the maximum vertical carrier confinement but also high thermal conductivity (340 W mK À1 ) and low thermal boundary resistance. So, it is expected to be reliable and stable when operating in harsh environments.…”
Section: Introductionmentioning
confidence: 99%